2016
DOI: 10.1111/mec.13876
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide sequence data suggest the possibility of pollinator sharing by host shift in dioecious figs (Moraceae, Ficus)

Abstract: The obligate mutualism of figs and fig-pollinating wasps has been one of the classic models used for testing theories of co-evolution and cospeciation due to the high species-specificity of these relationships. To investigate the species-specificity between figs and fig pollinators and to further understand the speciation process in obligate mutualisms, we examined the genetic differentiation and phylogenetic relationships of four closely related fig-pollinating wasp species (Blastophaga nipponica, Blastophaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 73 publications
(90 reference statements)
2
32
0
Order By: Relevance
“…An increasing number of fig tree species are known to be pollinated by two or more species of fig wasps, a feature that contrasts with the other well‐known nursery pollination system involving yucca moths and their yucca hosts (Smith, Drummond, Godsoe, Yoder, & Pellmyr, ; Yang et al, ; Yu, Tian, et al, ). Fig wasp colonization events followed by host switches have been reported among Ficus species (Wachi, Kusumi, Tzeng, & Su, ), but the northern, montane distribution of F. tikoua means that there is little range overlap with other Ficus species and fewer opportunities for host switching than would be the case for a tropical species. It is more common for fig wasps that share a host Ficus to be “cryptic” species that are difficult to tell apart morphologically (Chen et al, ; Darwell, Al‐Beidh, & Cook, ; Darwell & Cook, ; Rodriguez et al, ; Segar et al, ; Wachi et al, ; Wang, Cannon, & Chen, ; Yu, Tian, et al, ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…An increasing number of fig tree species are known to be pollinated by two or more species of fig wasps, a feature that contrasts with the other well‐known nursery pollination system involving yucca moths and their yucca hosts (Smith, Drummond, Godsoe, Yoder, & Pellmyr, ; Yang et al, ; Yu, Tian, et al, ). Fig wasp colonization events followed by host switches have been reported among Ficus species (Wachi, Kusumi, Tzeng, & Su, ), but the northern, montane distribution of F. tikoua means that there is little range overlap with other Ficus species and fewer opportunities for host switching than would be the case for a tropical species. It is more common for fig wasps that share a host Ficus to be “cryptic” species that are difficult to tell apart morphologically (Chen et al, ; Darwell, Al‐Beidh, & Cook, ; Darwell & Cook, ; Rodriguez et al, ; Segar et al, ; Wachi et al, ; Wang, Cannon, & Chen, ; Yu, Tian, et al, ).…”
Section: Discussionmentioning
confidence: 85%
“…Fig wasp colonization events followed by host switches have been reported among Ficus species (Wachi, Kusumi, Tzeng, & Su, ), but the northern, montane distribution of F. tikoua means that there is little range overlap with other Ficus species and fewer opportunities for host switching than would be the case for a tropical species. It is more common for fig wasps that share a host Ficus to be “cryptic” species that are difficult to tell apart morphologically (Chen et al, ; Darwell, Al‐Beidh, & Cook, ; Darwell & Cook, ; Rodriguez et al, ; Segar et al, ; Wachi et al, ; Wang, Cannon, & Chen, ; Yu, Tian, et al, ). They are typically sister species that have diverged during the history of their association with the plant (Souto‐Vilaros et al, ; Wang et al, ; Yang et al, ; Yu, Tian, et al, ).…”
Section: Discussionmentioning
confidence: 85%
“…We suggest that both temperature gradients and cloud cover will pose problems to dispersing fig wasps, indeed the largest genetic turnover is found between 1,200 m and 2,200 m. Horizontal distances are generally small between our study sites (<10 km) and isolation by distance is not found in F. arfakensis across larger distances (~80 km; Segar et al, ). Due to their short life‐span, assortative mating within the fig before emergence, and weak dispersal abilities, specifically for below‐canopy pollinators (Dev et al, ; Wachi et al, ), fig wasps seem to speciate along their host's range, perhaps aided by a resistance to Allee effects and genetic incompatibilities driven by Wolbachia (Yu et al, ). This structuring within wasps may eventually restrict pollen movement, promoting fig population structure and ultimately, host fig speciation (Cook & Segar, ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though fig wasps are generally highly mobile dispersers, relying on passive dispersal by wind (Ahmed, Compton, Butlin, & Gilmartin, ; Kobmoo, Hossaert‐Mckey, Rasplus, & Kjellberg, ; Liu, Compton, Peng, Zhang, & Chen, ), their mobility, and thereby the gene flow between their host plants, may sometimes be impaired. For instance, fig wasps associated with dioecious and under‐canopy fig species have limited flight ability (Venkateswaran, Kumble, & Borges, ), which is further compounded by the fact that dioecious fig trees tend to cluster into dense local populations (Dev, Kjellberg, Hossaert‐Mckey, & Borges, ; Wachi, Kusumi, Tzeng, & Su, ). In contrast, wide‐ranging monoecious species have little genetic structure over much of their ranges (Bain et al, ) and their pollinating wasps have been shown to be good dispersers (Venkateswaran et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The F. erecta genome characterized in this study provided insights into Ceratocystis canker resistance breeding strategies as well as identified responsible candidates for the resistance and sex determination genes. The genome resources will also be valuable for identifying the mechanisms underlying F. erecta resistance to other diseases or to pests such as nematodes (Hosomi, 1993) and may also contribute to our understanding of genome coevolution between F. erecta and the fig wasp ( Blastophaga nipponica ) (Wachi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%